Service quality and customer satisfaction towards banking sector: A case study of Bank Persatuan / Aliya Huda Ismail - Ismail, Aliya Huda (Faculty of Business Management, 2015)
Customer satisfaction is a key success of service institutions such as banking industry. The quality of service has become a feature of customer satisfaction. Day by day it has been proven that service quality is connected to customer satisfaction. The essential aim of this study is to look at most common constructs for quality of banking services, which influence customer satisfaction towards Bank Persatuan. Three factors of service quality such as employee’s attitude, banking system, and marketing strategy are considered as the main base of this study. The questionnaire was used to collect the data from 80 valid respondents by using convenience sampling method. The data was analysed by using SPSS. The final result based on multiple regressions showed that marketing strategy is significantly influence customer satisfaction towards Bank Persatuan.